Cote d'Ivoire : Enhanced Heavily Indebted Poor Countries Initiative: Completion Point Document and Multilateral Debt Relief Initiative; Press Release - Dorsey, Thomas (IMF Staff Country Reports; Country Report, 2012)
In April 2009, the Boards of Executive Directors of the International Development Association (IDA) and the International Monetary Fund (IMF) agreed that Cote d'Ivoire had met the requirements for reaching the decision point under the Enhanced Heavily Indebted Poor Countries (HIPC) Initiative. IDA and IMF staff are of the view that Cote d'Ivoire has made satisfactory progress in meeting the requirements to reach the completion point. IDA and IMF staff recommended that the Executive Directors of IDA and the IMF approve the completion point for Cote d'Ivoire under the Enhanced HIPC Initiative.